Heterogeneity in pineapple fruit quality results from plant heterogeneity at flower induction - Fassinou Hotegni, V. Nicodème; Lommen, Willemien J. M.; Agbossou, Euloge K.; Struik, Paul C. (Frontiers in Plant Science, 2014)
Heterogeneity in fruit quality constitutes a major constraint in agri-food chains. In this paper the sources of the heterogeneity in pineapple in the field were studied in four experiments in commercial pineapple fields. The aims were to determine (a) whether differences in pineapple fruit quality among individual fruits are associated with differences in vigor of the individual plants within the crop at the time of artificial flower induction; and (b) whether the side shoots produced by the plant during the generative phase account for the fruit quality heterogeneity. Two pineapple cultivars were considered: cv. Sugarloaf and cv. Smooth Cayenne. Plant vigor at the time of artificial flower induction was measured by three variates: the number of functional leaves, the D-leaf length and their cross product. Fruit quality attributes measured at harvest time included external attributes (weight and height of fruit, infructescence and crown) and internal quality attributes (total soluble solids, pH, translucent flesh). Results showed that the heterogeneity in fruit weight was a consequence of the heterogeneity in vigor of the plants at the moment of flower induction; that effect was mainly on the infructescence weight and less or not on the crown weight. The association between plant vigor variates at flower induction and the internal quality attributes of the fruit were poor and/or not consistent across experiments. The weight of the slips (side shoots), explained part of the heterogeneity in fruit weight, infructescence weight and fruit height in cv. Sugarloaf. Possibilities for reducing the variation in fruit quality by precise cultural practices are discussed.